Leaders’ Personal Wisdom and Leader–Member Exchange Quality: The Role of Individualized Consideration - Zacher, Hannes (Journal of business ethics, 2014)
Business scholars have recently proposed that the virtue of personal wisdom may predict leadership behaviors and the quality of leader–follower relationships. This study investigated relationships among leaders’ personal wisdom—defined as the integration of advanced cognitive, reflective, and affective personality characteristics (Ardelt, Hum Dev 47:257–285, 2004)—transformational leadership behaviors, and leader–member exchange (LMX) quality. It was hypothesized that leaders’ personal wisdom positively predicts LMX quality and that intellectual stimulation and individualized consideration, two dimensions of transformational leadership, mediate this relationship. Data came from 75 religious leaders and 1–3 employees of each leader (N = 158). Results showed that leaders’ personal wisdom had a positive indirect effect on follower ratings of LMX quality through individualized consideration, even after controlling for Big Five personality traits, emotional intelligence, and narcissism. In contrast, intellectual stimulation and the other two dimensions of transformational leadership (idealized influence and inspirational motivation) did not mediate the positive relationship between leaders’ personal wisdom and LMX quality. Implications for future research on personal wisdom and leadership are discussed, and some tentative suggestions for leadership development are outlined.